Association between sleep and fatigue in nurses who are engaged in 16 h night shifts in Japan: Assessment using actigraphy. Issue 4 (25th December 2018) - Kagamiyama, Hiromi; Sumi, Naomi; Yoshida, Yuko; Sugimura, Naotaka; Nemoto, Fumie; Yano, Rika
Abstract: Aim: To determine the association between sleep and fatigue in nurses who are working in a two‐shift system, including 16 h night shifts. Methods: Sixty‐one nurses were assessed on their sleeping and napping over 9 days, using actigraphy and a sleep diary. Work‐related feelings of fatigue were measured by using the "Jikaku‐sho shirabe" questionnaire and the Cumulative Fatigue Symptoms Index. Results: The main night‐time sleep started after 00:00 hours in half of the participants and the average start and end times were significantly delayed among the participants in their 20s, compared to those in their 40s . Although 90% of the participants napped during and/or after a night shift, only 50.8% napped for >2 h during their shift and 32.8% napped in the morning after a night shift. In the high‐fatigue group, significantly more nurses went to sleep after 00:25 hours than before 00:26 hours the night after a night shift. Furthermore, those nurses who napped for >2 h during their night shift exhibited a significantly lower rate of some cumulative fatigue symptoms, compared to those who did not. In addition, a combination of napping in the morning after a night shift and beginning the following night‐time sleep before 00:26 hours were associated with a significant decrease in fatigue symptoms. Conclusions: Naps at an appropriate time and of an appropriate duration, along with the practice of beginning the night‐time sleep early after a night shift, might relieve cumulative mental fatigue in nurses who are working 16 h night shifts.